Adhesion concepts and techniques for laboratory-processed indirect dental restorations - Omar Abdullah Alsadon (Elsevier, 2022)
The purpose of this review was to analyze the existing literature on surface conditioning of the veneering surface of substructure restorative materials in dental laboratories. New technologies are constantly improving the treatment options for fabricating dental restorations, and new materials and adhesion procedures are being offered to clinicians and dental technologists. To establish a reliable adhesion between the veneer and substructure in the dental laboratory, various surface treatment procedures and adhesion promoters are employed. The composition of a material influences the adhesion approach selected, and implementing a reliable adhesion strategy is critical for the predictability of veneered indirect dental restorations. However, surface treatment of a wide range of available material options can be challenging. Therefore, understanding various adhesion processes for different restorative materials may assist dental technologists in selecting the best and appropriate surface conditioning protocol for each dental restorative material category.